Strategi Optimalisasi Pertumbuhan Usaha Mikro: Dampak Pelatihan Kewirausahaan, Kualitas Pelayanan, dan Pemasaran Digital terhadap Peningkatan Pendapatan di Pantai Wediombo - Daniel Joel Immanuel Kairupan; Dicky Setyo Purnomo (Universitas Sahid, 2024)
This study aims to analyze the effect of entrepreneurship training, service quality, and digital marketing on increasing micro-entrepreneurs income in the Wediombo Beach tourist area. As a developing tourist destination, Wediombo Beach is the center of local economic activities that depend on the tourism sector, so increasing the income of micro-entrepreneurs is important for the sustainability of the regional economy. This study uses a quantitative approach with a survey method involving 60 respondents of Wediombo Beach micro-entrepreneurs. The analysis tool uses SmartPLS 3.2.9. The conclusion of this study shows that developing entrepreneurial skills, improving service quality, and optimizing digital marketing are important factors that can increase the income of micro-entrepreneurs in the Wediombo Beach tourist area. This study provides practical implications for local governments and stakeholders in designing programs that support strengthening the local economic sector through training and application of technology in marketing.